Skeletal age and explosive strength in young volleyball players - Petrus Gantois; Vanessa C. M. Pinto; Kezianne R. de Castro; Paulo V. João; Paulo M. S. Dantas; Breno Guilherme G. A. T. Cabral (Universidade Federal de Santa Catarina, 2017)
Identifying diferent anthropometric, physiological and motor aspects is essential to obtain success in sports practice. However, these components may be developed in same age subjects diferently, in part due biological development. he aim of the study was compare and correlate the explosive strength to biological maturation by sex, obtained by estimation of skeletal age based on anthropometric variables. he sample consisted of 239 subjects of both sexes, aged 10 to 13 years. Maturation was assessed by skeletal age predictive equation and upper and lower limbs explosive strength using medicine ball throw test and vertical jump, respectively. Skeletal age was assessed by skeletal age using a predictive anthropometrical based equation. Upper and lower limbs explosive strength were evaluated by medicine ball throwing test and vertical jump test, respectively. Post hoc analysis showed delayed biological development subjects had worst medicine ball throwing test performance than accelerated boys (p=0.001; d=0.96) and girls (p< 0.01; d= 2.01); regarding to vertical jump test, worst performance was also detected to maturational delayed boys when compared to accelerated ones (p=0.24; d=1.1) and girls (p=0.007; d=0.75). Regression analysis showed skeletal age explained variance of 36% and 19.2% for boys and 45.2% and 16.1% for girls upper and lower limbs explosive strength. Skeletal age is positively related to upper and lower limbs explosive strength and show higher performance for accelerated biological development young players when compared to delayed ones, independently from sex.